2022
DOI: 10.1021/acsanm.2c00105
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant α-Mangostin Coated Woven Polycaprolactone Nanofibrous Yarn Scaffold for Cardiac Tissue Repair

Abstract: Electrospun nanofibrous scaffolds are one of the most extensively used proven candidates for scaffold-based tissue engineering applications due to their excellent nanoscale architecture and tailorable nature. Despite the advantages of electrospun scaffolds, drawbacks such as low mechanical strength and densely packed nanofibers lead to decreased cell infiltration, preventing diffusion of nutrients and gases. To overcome these shortfalls, nanofiber yarns formed by directly twisting thousands of electrospun nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Subsequently, the cells were stained with Hoechst dye for 10 min to visualize the cell nuclei on the scaffolds. The scaffolds were gently washed twice with DPBSA and examined using a Fluorescent microscope [ 38 ]. The cell count from different images at different locations for each group (SF and SF-QFM) at 2–6 days was analyzed using ImageJ software version 1.54.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the cells were stained with Hoechst dye for 10 min to visualize the cell nuclei on the scaffolds. The scaffolds were gently washed twice with DPBSA and examined using a Fluorescent microscope [ 38 ]. The cell count from different images at different locations for each group (SF and SF-QFM) at 2–6 days was analyzed using ImageJ software version 1.54.…”
Section: Methodsmentioning
confidence: 99%
“…Richard et al recently investigated therapeutic agent-coated PCL-based nanofiber-woven scaffolds for heart regeneration [ 144 ] ( Figure 10 ). The woven scaffold, manufactured by electrospinning with a collecting device to yarn the fibers followed by weaving [ 145 ], exhibited suitable mechanical strength and could serve as an appropriate structure for cell adhesion.…”
Section: Biomedical Applications Of the Therapeutic Agent-loaded Fibr...mentioning
confidence: 99%
“…11 As such, considerable progress has been made in the development of microenvironment modulating biomaterials for cardiac applications, with a major focus on antioxidant materials that can scavenge ROS within diseased sites. [12][13][14][15][16][17][18][19][20][21] AA, commonly known as vitamin C, is a non-toxic antioxidant that has been researched extensively for the treatment of myocardial infarction. [22][23][24] A recent systematic review indicated that AA may decrease oxidative stress and inflammation, thus preserve cardiac function, when administered prior to reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials to date have only administered antioxidants orally or intravenously, however targeting oxidative stress directly within the diseased site using implantable or injectable materials may more effectively reduce local oxidative stress 11 . As such, considerable progress has been made in the development of microenvironment modulating biomaterials for cardiac applications, with a major focus on antioxidant materials that can scavenge ROS within diseased sites 12–21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation